Systemic amyloidosis AL with temporal artery involvement revealing lymphoplasmacytic malignancy in a man presenting as polymyalgia rheumatica. Issue 2 (February 1993) - Lafforgue, P; Senbel, E; Figarella-Branger, D; Boucraut, J; Horschowsky, N; Pellissier, J F; Acquaviva, P C
Abstract : A 68 year old man presented with a clinical and biological picture that suggested polymyalgia rheumatica. Temporal artery biopsy disclosed no inflammatory change but massive light chain amyloid deposits in the media. Further exploration showed a malignant lymphoplasmacytic haemopathy with a triclonal gammopathy and a muscular, rectal, and probable cardiac amyloidosis. Cryoglobulinaemia and high concentrations of soluble interleukin 2 receptor (sIL-2R) were also found. This is the fifth case with confirmed involvement of the temporal artery. The especially high sIL-2R concentration was thought to reflect the tumour mass rather than lymphocyte activation.